IMPROVING STUDENT'S LEARNING OUTCOMES THROUGH THE TGT-TYPE COOPERATIVE LEARNING MODEL IN IPS COURSES IN CLASS IV SDN 18 BALAESANG - Rahmawati Samu; Herlina Herlina; Surahman Wilade (Jurnal Dikdas, 2022)
The purpose of this study was to improve student learning outcomes through the TGT Cooperative Learning Model in Class IV SDN 18 Balaesang. The research was conducted in II cycles and applied to the fourth-grade students of SDN 18 Balaesang with a total of 22 students, consisting of 13 female students and 9 male students. The data were collected by means of tests and observations. This type of research is classroom action research, the learning outcomes of the first cycle of classical learning completeness of 60% and the second cycle of 90.90%. The percentage of teacher activity results in the first cycle of 72.72% is categorized as sufficient and the second cycle of 80% is categorized as good. This shows that if the TGT (team games tournament) learning method is applied it can improve student learning outcomes in social studies subjects in grade IV SDN 18 Balaesang.